2021
DOI: 10.1186/s12931-021-01840-7
|View full text |Cite
|
Sign up to set email alerts
|

Circ_PIP5K1A regulates cisplatin resistance and malignant progression in non-small cell lung cancer cells and xenograft murine model via depending on miR-493-5p/ROCK1 axis

Abstract: Background Chemoresistance limits the therapeutic effect of cisplatin (DDP) on non-small cell lung cancer (NSCLC). Circular RNAs (circRNAs) function as important regulators in chemoresistance. This study aimed to explore the regulation of circRNA Phosphatidylinositol-4-Phosphate 5-Kinase Type 1 Alpha (circ_PIP5K1A) in DDP resistance. Methods The expression analysis of circ_PIP5K1A, micoRNA-493-5p (miR-493-5p) and Rho Associated Coiled-Coil Containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Recently, it has been shown that miR-493-5p regulates the progression of several diseases, especially cancer. It was shown that miR-493-5p/ROCK1 affects malignant progression and cisplatin resistance of non-small cell lung cancer cells via circ_PIP5K1A in a xenograft murine model [12]. However, there has only been one study on the role of miR-493-5p in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that miR-493-5p regulates the progression of several diseases, especially cancer. It was shown that miR-493-5p/ROCK1 affects malignant progression and cisplatin resistance of non-small cell lung cancer cells via circ_PIP5K1A in a xenograft murine model [12]. However, there has only been one study on the role of miR-493-5p in OA.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-493-5p inhibits glioma progression by decreasing E2F3-mediated P53 and PI3K/AKT pathway dysfunction (Liu H. et al, 2022). Some studies have shown that mir-493-5p overexpression plays a negative regulatory role in esophageal cancer, osteosarcoma, cervical cancer, nonsmall cell lung cancer, and other malignancies by inhibiting cell proliferation/ migration/invasion (Feng et al, 2021;Wang et al, 2021;Liu Q. et al, 2022;Huang et al, 2022). Downregulation of miR-1285-3p reversed the effects of weak expression of circRNA_400029 on the progression and apoptosis of cervical cancer cells (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 14 miRNAs identified here, rno-miR-493-5p is reported to be associated with cancer cells [ [32] , [33] , [34] ]. In addition, our KEGG pathway analysis also indicated that miRNA21, 1, 34a, 34c, 133, 133a, and Let-7c also take part in the cancer pathway ( Fig.…”
Section: Discussionmentioning
confidence: 99%